Relaxation damage control via fatigue-hydraulic fracturing in granitic rock as inferred from laboratory-, mine-, and field-scale experiments - Arno Zang (Nature Portfolio, 2021)
Abstract The ability to control induced seismicity in energy technologies such as geothermal heat and shale gas is an important factor in improving the safety and reducing the seismic hazard of reservoirs. As fracture propagation can be unavoidable during energy extraction, we propose a new approach that optimises the radiated seismicity and hydraulic energy during fluid injection by using cyclic- and pulse-pumping schemes. We use data from laboratory-, mine-, and field-scale injection experiments performed in granitic rock and observe that both the seismic energy and the permeability-enhancement process strongly depend on the injection style and rock type. Replacing constant-flow-rate schemes with cyclic pulse injections with variable flow rates (1) lowers the breakdown pressure, (2) modifies the magnitude-frequency distribution of seismic events, and (3) has a fundamental impact on the resulting fracture pattern. The concept of fatigue hydraulic fracturing serves as a possible explanation for such rock behaviour by making use of depressurisation phases to relax crack-tip stresses. During hydraulic fatigue, a significant portion of the hydraulic energy is converted into rock damage and fracturing. This finding may have significant implications for managing the economic and physical risks posed to communities affected by fluid-injection-induced seismicity.